Thermodynamic analysis of DNA complexes with methylene blue, ethidium bromide and Hoechst 33258 - Vardevanyan, P.O.; Antonyan, A.P.; Hambardzumyan, L.A.; Shahinyan, M.A.; Karapetian, A.T. (Вiopolymers and Cell, 2013)
Aim. To investigate the thermodynamic characteristics of complexes of calf thymus double-stranded DNA with methylene blue (MB), ethidium bromide (EtBr) and Hoechst 33258 (H33258). Methods. The binding of MB with double-stranded DNA was observed by UV-melting method. Results. Several types of MB binding to DNA-intercalating, semi-intercalating and electrostatic with DNA phosphate backbone, have been revealed at low concentrations of Na+ (2 mM). At high concentrations of cations and low ratios of rb = [ligand]/[DNA] ( 0.05), the molecules of ligand semi-intercalate into the space between adjacent bases. At higher concentrations of ligand the main mode becomes electrostatic binding of MB to DNA phosphate groups. Conclusions. The comparison of thermodynamic characteristics of DNA-MB complexes with those of EtBr and H33258 indicates that there is more than one mode of binding ligands to DNA: besides nonspecific, external electrostatic binding with phosphate groups, intercalation and semi-intercalation modes of interaction coexist.